Using blended learning to facilitate large room seminar provision in the era of TEF: reflections from a year two cultural geography module. Issue 2 (3rd April 2019) - Jenkins, Lloyd
ABSTRACT: The introduction of the Teaching Excellence Framework (TEF) in 2016 has placed the practice and quality of teaching centre of the UK university agenda, with concerns around contact, delivery, research/teaching balance and facility support framing debates within institutions. Situating the implementation of blended learning on a year 2 cultural geography in the broader context of these discussions, this paper explores some of the challenges and opportunities this approach has in addressing some of these broader concerns, whilst improving student engagement and performance.